PENGARUH MOTIVASI TERHADAP KINERJA USAHA MIKRO KECIL MENENGAH PADA USAHA DAGANG DESA ORAHILI GOMO KECAMATAN GOMO - Suniati Tafonao (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study was to determine the effect of motivation on the performance of micro, small and medium enterprises in the Orahili Gomo Village Trading Business, Gomo District. The type of research used is a quantitative type. The type of data used in this study is the type of primary data, namely data obtained directly from the respondents. The data collection technique is a questionnaire by providing a list of statements to the respondents to fill out. The data analysis method used is simple regression analysis. Based on the research results of testing the hypothesis with a tcount value of 3.313> ttable 1.549, small and Medium Enterprises in the trading business of Orahili Gomo Village, Gomo District. It can be concluded from this study that there is a motivational influence on the performance of Micro, Small and Medium Enterprises in the trading business of Orahili Gomo Village, Gomo District. The suggestions for this research are (1) To improve business performance, especially in Orahili Village, Gomo District, the government should provide motivation for every micro-entrepreneur through loans with relatively low interest by facilitating the community's economic turnover. (2) The concern of micro business actors in carrying out their activities should be increased from before to increase sales volume.